The Influence of Service Quality and Customer Segmentation on Service Usage Decisions at PT. Samas Agung Tunggal Perkasa - Ricky Nelson; Sarifuddin T; Marwana (Universitas Muhammadiyah Palu, 2026)
With the increase in domestic trade activity and the development of e-commerce, the demand for expedition services, particularly by sea, has also increased. One company playing a role in this sector is PT Pelayaran Samas Agung Tunggal Perkasa (SAMAS), which provides inter-island shipping services to Jakarta, Surabaya, Palu, Kendari, and Toli-Toli. However, over time, the company has faced various challenges, particularly increased competition among similar companies due to the growing number of businesses in the expedition services industry. This situation underpins the purpose of this study: to analyze the influence of service quality and customer segmentation on the decision to use PT SAMAS's services. This study used a quantitative method with multiple linear regression analysis. Data collection was conducted through questionnaires distributed to PT SAMAS customers. The results showed that service quality significantly influenced the decision to use services, as evidenced by a calculated t-value of 2.475 > t-table 1.996. Furthermore, customer segmentation also significantly influenced the decision to use services, with a calculated t-value of 4.572 > t-table 1.996. Thus, it can be concluded that service quality and customer segmentation have an influence on the decision to use PT SAMAS expedition